Manakah Antara Pajak dan Zakat yang Lebih Efektif dalam Pengentasan Kemiskinan Menurut Mahasiswa Baru FEB UB - Azka Maulana; Diva Armaita Sary; Diva Yonala Choirun Nisya’; Yuniar Rizqi Amanda; Ahmad Ferdiansyah Putra; Cindy Putri Nadia; Arif Mustapa (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Poverty is a long-standing problem across countries. Various kinds of efforts to alleviate poverty have been carried out by the government, of course with huge amounts of spending. The collection of funds to the society for social assistance financing can only be done through taxes and zakat. Research on the differences between tax and zakat has been widely conducted, so research on students' views on tax and zakat is needed to find out students' understanding of tax and zakat. This study used descriptive quantitative methods using data collection methods through questionnaire surveys. The results showed that new year college students who chose zakat more effectively or taxes were more effective in terms of poverty alleviation were almost balanced. However, data from BAZNAS and the Ministry of Finance shows that tax has more advantages in the amount of revenue it generates. In fact, several studies have shown empirical evidence that taxes are superior to zakat in terms of poverty alleviation. The results of this study can be used to improve the understanding of zakat and tax as poverty alleviation tools.